Evaluation of Genetic Variation in Hybrid Catfish (Sangkuriang × Thai) Employing PCR-RAPD Markers - Kurnia Anggraini Rahmi; Putriku Nadzira Sativa; Alimuddin Alimuddin; Dinar Tri Soelistyowati (Jurnal Perikanan UGM (Journal of Fisheries Sciences), 2026)
Hybridization is the process of crossing individuals with different genotypes to produce offspring with superior traits. In this study, Sangkuriang catfish were crossed with introduced Thai catfish to obtain heterosis in hybrid seeds. The objective was to analyze the genetic diversity of these hybrid seeds using the PCR-RAPD method. Specifically, the primers OPA-13, OPB-08, OPC-19, and OPD-02 were used. Crossbreeding involved Sangkuriang female and Thai male broodstock, with four pairs of broodfish used via a semi-natural spawning method. After spawning, hybrid seeds from each pair were reared separately in containers under uniform conditions for 1.5 months. DNA samples were then collected from the fin tissue of each replicate of the crosses, and were grouped according to size categories: large (7-8 cm), medium (5-6 cm), small (3-4 cm), and broodstock, with 30 samples per size category for each replicate. The results revealed a polymorphism percentage of 72.95-93.88%, heterozygosity values of 0.167-0.232, and an average genetic distance among hybrid seeds from the three size categories and broodstock ranging from 0.001-0.018.